Le najboljše od bobrov - praktični pristopi za ohranitev pozitivnih vplivov bobra in zmanjševanje konfliktov - Vochl, Saša (Gozdarski vestnik, 2017)
Beaver (Castor fiber) as a key stone species has a profound impact on biodiversity. Tree felling, dam building and burrowing can also result in human-beaver conflicts. Beavers return to Slovenia in 1998 and with their number increasing we expect an increase in the number of conflicts. Slovenia has no knowledge nor experience in dealing with flood prevention caused by beaver dams. Removing beaver from the environment provides a short-term solution as new beavers will occupy the empty habitat and conflict will continue. It is possible to prevent negative impacts and keep all the benefits of beaver presents by using non-invasive methods. People tolerance to beaver presents greatly depends on the immediate and effective resolving of beaver-human conflicts.
Keywords: conflict prevention; preprečevanje konfliktov; beaver; bobri; bobrov jez; beaver dam; biodiversity management; upravljanje z biotsko pestrostjo; vplivi na ekosistem; impacts on ecosystem